2019
DOI: 10.21203/rs.2.15426/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Management practice, and treatment outcome and its associated factors among hospitalized stroke patient at Ambo University Referral Hospital, Ethiopia: an Institutional Based Cross Sectional Study

Abstract: Background: Although stroke has been consistently reported as one of the three leading causes of morbidity and mortality in the past few years in Ethiopia, there is a paucity of data regarding to stroke treatment outcomes and associated factors. Hence, this study was aimed to assess management practice, and treatment outcome and its associated factors among hospitalized stroke patients.Method an institutional based cross sectional study was conducted among 111 hospitalized stroke patients in the medical ward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…This study showed that the in-hospital mortality was 31.2% and 51.4% of the patients who died in the hospital were patients with ischemic stroke. It was also found that the proportion of patients who had an acute hemorrhagic stroke was higher when compared with previous studies conducted in other regions in Ethiopia 17 and some African countries. 22 , 23 This difference could be due to the variations in the risk factors for stroke.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…This study showed that the in-hospital mortality was 31.2% and 51.4% of the patients who died in the hospital were patients with ischemic stroke. It was also found that the proportion of patients who had an acute hemorrhagic stroke was higher when compared with previous studies conducted in other regions in Ethiopia 17 and some African countries. 22 , 23 This difference could be due to the variations in the risk factors for stroke.…”
Section: Discussioncontrasting
confidence: 45%
“…In Ethiopia, a few studies have been conducted on stroke. [15][16][17][18][19] However, no study has been conducted in the eastern region where the burden of stroke and cardiovascular disease risk factors could be different from other regions. Hence, this study aimed to assess in-hospital outcomes and associated factors in stroke patients admitted to Hiwot Fana Specialized University Hospital (HFSUH) in eastern Ethiopia…”
Section: Introductionmentioning
confidence: 99%
“…The study was conducted among the following three randomly selected hospitals. Ambo University Referral Hospital is teaching hospital located at in the city of Ambo, the capital of East Showa, and 114 km from the Ethiopian capital Addis Ababa and serves more than 2 catchment areas.5 million peoples (22). Nekemte Comprehensive Specialty Hospital is located in the town of Nekemte, East Wollega, Ethiopia and provide services to approximately 5 million peoples (23,24).…”
Section: Study Area and Periodmentioning
confidence: 99%
“…A conceptual framework on factors associated with in-hospital mortality among patient undergone laparotomy adapted and developed from (7,14,15,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Ethical Approvalmentioning
confidence: 99%
“…The number of participants in each study ranged from 73 to 503. The most retrieved studies (n = 8) were from Oromia [29][30][31][32][33][34][35][36] followed by Addis Ababa (n = 7) [37][38][39][40][41][42][43], Amhara (n = 7) [44][45][46][47][48][49][50], Tigray region (n = 4) [51][52][53][54], and Southern Nations Nationalities and People's (SNNP) (n = 1) [55].…”
Section: Study Characteristicsmentioning
confidence: 99%